Effect of lactose and milk protein on thermal resistance of Enterococcus faecium NRRL B-2354 and Salmonella in dairy powders - Ahmad, Nurul Hawa; Marks, Bradley P.; Ryser, Elliot T. (International Association for Food Protection, 2022)
Microbial challenge studies using nonpathogenic surrogates provide a practical means for validating thermally based pathogen controls for low-moisture foods. Because the relative thermal resistance, or kill ratio, of Enterococcus faecium NRRL B-2354 (a nonpathogenic surrogate) to Salmonella is greatly influenced by food composition, this study assessed relative thermal resistance of a five-strain Salmonella cocktail and E. faecium in skim milk powder (SMP), lactose-free skim milk powder (LSMP), 90% milk protein isolate (MPI), and lactose powder (LP). The impact of sugar composition (lactose versus glucose-galactose) on resuscitation of bacterial survivors, by using SMP and LSMP, was also determined. Dairy powders were inoculated with agar-grown cultures, mixed, preequilibrated at 0.25 water activity (aw), ground to achieve homogeneity, reequilibrated, and subjected to isothermal treatment. After enumeration on nonselective differential media, log-linear and Bigelow models were fit to the survivor data via one-step global regression. The aw changes and glass transition temperature were assessed at elevated temperatures by using uninoculated, equilibrated powder samples. Estimated D90°C-values were approximately two times higher for E. faecium (P < 0.05) than for Salmonella in SMP, LP, and MPI, but statistically similar (P > 0.05) in LSMP. Addition of sugars to recovery media did not influence survivor resuscitation from heat-treated SMP and LSMP, confirming that microbial inactivation was impacted primarily by the thermal treatment, not the recovery step. Thermally induced changes in aw were seen only for LP and MPI, with the glass transition temperature observed only for SMP and MPI. In conclusion, rather than always requiring greater lethality of E. faecium than Salmonella, these findings suggest that sufficient pathogen controls for low-moisture foods can also be validated by thoroughly documenting the appropriate kill ratios of E. faecium to Salmonella.